Comparison of Oncologic Outcomes between Carbon Ion Radiotherapy and Stereotactic Body Radiotherapy for Early-Stage Non-Small Cell Lung Cancer - Miyasaka, Yuhei (Cancers (Basel), 2021)
SIMPLE SUMMARY: Lung cancer is a leading cause of cancer-related death. Stereotactic body radiotherapy (SBRT) is the standard treatment for inoperable early-stage non-small cell lung cancer (NSCLC). Carbon ion radiotherapy (CIRT) is a safe and effective treatment for early-stage NSCLC. However, there is no direct comparison study between these treatments. The present study aimed to compare oncologic outcomes after CIRT and SBRT for early-stage NSCLC in a single-institutional and contemporaneous cohort. We demonstrated favorable overall survival and local control in the CIRT group compared to those in the SBRT group using log-rank tests and Cox regression analyses for 89 patients. In addition, these results were validated in propensity score-adjusted analyses. The present retrospective comparison study showed a positive efficacy profile of CIRT, which is beneficial in the management of early-stage NSCLC. ABSTRACT: Lung cancer is a leading cause of cancer-related deaths worldwide. Radiotherapy is an essential treatment modality for inoperable non-small cell lung cancer (NSCLC). Stereotactic body radiotherapy (SBRT) is the standard treatment for early-stage NSCLC because of its favorable local control (LC) compared to conventional radiotherapy. Carbon ion radiotherapy (CIRT) is a kind of external beam radiotherapy characterized by a steeper dose distribution and higher biological effectiveness. Several prospective studies have shown favorable outcomes. However, there is no direct comparison study between CIRT and SBRT to determine their benefits in the management of early-stage NSCLC. Thus, we conducted a retrospective, single-institutional, and contemporaneous comparison study, including propensity score-adjusted analyses, to clarify the differences in oncologic outcomes. The 3-year overall survival (OS) was 80.1% in CIRT and 71.6% in SBRT (p = 0.0077). The 3-year LC was 87.7% in the CIRT group and 79.1% in the SBRT group (p = 0.037). Multivariable analyses showed favorable OS and LC in the CIRT group (hazard risk [HR] = 0.41, p = 0.047; HR = 0.30, p = 0.040, respectively). Log-rank tests after propensity score matching and Cox regression analyses using propensity score confirmed these results. These data provided a positive efficacy profile of CIRT for early-stage NSCLC.